(untitled) (Quintú Quimün. Revista de lingüística, 2024)
Dicen que escapó este mozo Del sueño de los sin jeta Que a los poderosos reta Y ataca a los más villanos Sin más armas en la mano Que un diez en la camiseta Maradó, Los piojos We chose as an epigraph a song that refers to the number ten, the emblematic symbol of Diego (Maradona), given that this is the tenth edition of Quintú Quimün. It is amazing to have reached this number of publications and, even more so, to continue projecting a free, open access linguistics journal from these souths. Although it has been an exhausting year due to the constant fight in defense of the public university and the need to explain again and again the importance of guaranteeing national scientific development, we have accompanied, cared for, consoled and motivated each other to gather strength and move forward. For 2025, in fact, we have proposed two calls that are already announced on our website. But let’s get to what we have to show today. In the section of general articles, we have a work by Clelia Méndez (Universidad Nacional del Litoral) on a sociolinguistic situation in General Güemes (Salta), while the article by Nazira Günther (Universidad Nacional de Córdoba) focuses on forms of treatment using the social network Twitter (current X) as a corpus. In addition, we offer a dossier titled Language and Cognition: Interdisciplinary Studies on Language Processing and had Álvaro Cabana (University of the Republic, Uruguay) and Gabi Zunino as editors. The dossier has an introduction by the editors and five articles. It not only presents an updated overview of processing studies, but also brings together researchers from different universities in South America. In the interview section, Cintia Carrió talks with Andrey Nikulin (Federal University of Goiás, Brazil), who tells us about his academic career, his work with speakers of minority languages ​​and the impact of the Linguistics Olympics on his career. The review was by Guillermina Piatti from the National University of La Plata. On this occasion, the book chosen was Teaching-learning of foreign languages: classic topics from new perspectives by Estela Klett. Both the book and Guillermina’s review constitute extremely valuable material for those who work and research on topics related to the teaching of additional languages. Finally, in the dissemination section, our beloved Linguistics that does not bite, Antonio Fábregas (Norwegian University of Science and Technology, Norway) offers us a fun essay on the role of biases in that impulse that people have to correct the form to talk about others. Continue reading...